164k views
1 vote
If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the second equation is substituted into the first equation. 3x + 2y = -21 x - 3y = 4 (5 points) 3(3y + 4) + 2y = -21 3(-3y + 4) + 2y = -21 3x + 2(3y + 4) = -21 3x + 2(-3y + 4) = -21

2 Answers

4 votes

Answer:

3(3y+4)+2y=-21

Explanation:

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the second equation is substituted into the first equation.

3x + 2y = -21

x - 3y = 4

Solve the second equation for x

x-3y= 4

Add 3y on both sides

x= 4+ 3y

Now replace 4+3y for x in first equation

3(4+3y) +2y= -21

3(3y+4)+2y=-21

User Naseefo
by
4.7k points
4 votes

\left\{\begin{array}{ccc}3x+2y=-21\\x-3y=4&|Add\ 3y\ to\ both\ sides\end{array}\right\\\\\left\{\begin{array}{ccc}3x+2y=-21\\x=4+3y\end{array}\right\\\\substitute\ into\ the\ first\ equation\\\\3(4+3y)+2y=-21\\\\\boxed{Answer:\ 3(3y+4)+2y=-21}
User MADHAVI KUMARI
by
5.1k points